On some sea cucumbers from Ghana (Echinodermata: Holothuroidea) with descriptions of a new genus and one new species - Thandar, Ahmed S.; Mjobo, Sifiso (Zootaxa, 2014)
This paper reports on some sea cucumbers (Holothuroidea) in the collections of the NHMUK, taken off the coast of Ghana. Most result from collections around Accra during the years 1949–52. A couple of other species are included. Altogether six species are here reported, viz. Holothuria (Holothuria) dakarensis Panning, 1939; Holothuria (Semperothuria) imitans Ludwig, 1875; Holothuria (Vaneyothuria) lentiginosa lentiginosa (von Marenzeller,1893); Stereoderma congoana (Heding, 1935); Ocnus cruciformis Thandar n. sp. and Leptopentacta cabindaensis (Cherbonnier, 1949) herein transferred to a new genus Cherbocnus Thandar erected for this purpose. Another West African species, Cladodactyla monodi Cherbonnier, 1950 is referred to Stereoderma. All cucumariids are West African forms whereas the holothuriids are shared with the North-West Atlantic Ocean.